Faktor-Faktor Yang Memengaruhi Return Saham Perusahaan LQ-45 - Poppy, Ribka; Swastika, Endang; Ritha, Henny (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study aims to analyze the Factors Affecting the stock returns of the LQ 45 company for 2017-2021. The research sample consisted of 7 manufacturing companies and data sources were obtained from the 2017-2021 financial statements. This type of research data uses quantitative data, and the data collection method is documentation. Technique analysis used panel data regression analysis. The results show the selected FE method and prove that ROA has a positive effect on stock returns, DER has a positive effect on stock returns, and PER has a negative effect on stock returns of the LQ 45 company for 2017-2021.